Подождите немного. Документ загружается.

σ
2
ε ∼ N(0, σ
2
I)
β
ˆ
β β
ˆε
i
= e
i
= Y
i
− x
i·
ˆ
β, i = 1, . . . , n,
e = (e
1
, . . . , e
n
)
T
= Y − X
ˆ
β = Y −
ˆ
Y.
ˆ
Y = X
ˆ
β Y X
ˆ
β
n
X
i=1
e
2
i
= e
T
e → min .
ˆ
β = (X
T
X)
−1
X
T
Y.
X
T
X
β
β
Y = α + βX + ε
ˆ
β =
P
n
i=1
(X
i
− X)(Y
i
− Y )
P
n
i=1
(X
i
− X)
2
, ˆα = Y −
ˆ
βX,
Y = [
P
n
i=1
Y
i
] /n X = [
P
n
i=1
X
i
] /n Y X

σ
2
ˆσ
2
= s
2
=
1
n − k
n
X
i=1
e
2
i
=
e
T
e
n − k
.
ˆ
β E(
ˆ
β
ˆ
β
T
)
d
Var(
ˆ
β) =
b
E(
ˆ
β
ˆ
β
T
) = s
2
(X
T
X)
−1
.
b
E
s
ˆ
β
j
= s
q
(X
T
X)
−1
jj
.
α
t
α
n−k
n − k
α n − k
β
j
ˆ
β
j
− t
α
n−k
s
ˆ
β
j
≤ β
j
≤
ˆ
β
j
+ t
α
n−k
s
ˆ
β
j
.
β
j
= 0
t =
ˆ
β
j
s
ˆ
β
j
n − k
β
j
= β
∗
j
t
∗
=
ˆ
β
j
− β
∗
j
s
ˆ
β
j
,
σ
2
(n − k)s
2
χ
2
α/2
≤ σ
2
≤
(n − k)s
2
χ
2
1−α/2
,
χ
2
α/2
χ
2
1−α/2
χ
2
n − k

Y
SST =
n
X
i=1
(Y
i
− Y )
2
= Y
T
Y − nY
2
,
SSE =
n
X
i=1
(
ˆ
Y
i
− Y )
2
=
ˆ
β
T
X
T
Y − nY
2
=
ˆ
β
T
X
T
X
ˆ
β − nY
2
SSR = e
T
e.
SST = SSE + SSR.
Y
R
2
=
SSE
SST
= 1 −
e
T
e
Y
T
Y − nY
2
.
s
y
=
SST
n − 1
=
Y
T
Y − nY
2
n − 1
Y
Y
˜
R
2
˜
R
2
= 1 −
n − 1
n − k
(1 − R
2
).
X

F
F =
R
2
/(k − 1)
(1 − R
2
)/(n − k)
,
F [k −1, n −k]
β
2
= β
3
= ··· = β
k
= 0
α
F
α
k−1,n−k
α k −1
n−k
> 0.9
R
2
> 0.3
γ = w
T
β w
α
ˆγ − t
α
n−k
s
ˆγ
≤ γ ≤ ˆγ + t
α
n−k
s
ˆγ
,
ˆγ = w
T
ˆ
β, s
2
ˆγ
= w
T
s
2
(X
T
X)
−1
w.
σ
2
ˆ
β
j
=
σ
2
(1 − R
2
j
)
n
P
i=1
(X
ji
− x
·j
)
,
x
·j
X
j
j
X R
2
j
X
j

R
2
j
ˆ
β
j
t
VIF
j
=
1
1 − R
2
j
.
i
ˆ
β(i) = [X(i)
T
X(i)]
−1
X(i)
T
Y(i),
(i) i
e
i
(i) = Y
i
− x
i·
ˆ
β(i),
Var(e
i
(i)) = s
2
(i)(1 + x
i·
[X(i)
T
X(i)]
−1
x
T
i·
).
e
i
(i)/
p
Var(e
i
(i))
2
n
m
β X
0
(n ×k) Y
0
(n ×1)
A
0
= (X
T
0
X
0
)
−1
B
0
= X
T
0
Y
0
m
X
1
(m ×k) Y
1
(m ×1) X((m + n) ×k)
Y((m + n) × 1)
A = (X
T
X)
−1
= A
0
− A
0
X
T
1
[I + X
1
A
0
X
T
1
]
−1
X
1
A
0
,
B = X
T
Y = B
0
+ X
T
1
Y
1
,
ˆ
β = (X
T
X)
−1
X
T
Y = AB.
β
1
. . . β
k
g(Y ) = β
1
+ β
2
f
2
(X
2
, . . . , X
k
) + ··· + β
k
f
k
(X
2
, . . . , X
k
) + ε,

g f
2
. . . f
k
Y
∗
= g(Y ) X
∗
2
= f
2
(X
2
, . . . , X
k
) . . . X
∗
k
=
f
k
(X
2
, . . . , X
k
) θ
1
. . . θ
k
θ
1
. . . θ
k
β
1
. . . β
k
J
r
11
β
1
+ r
12
β
2
+ ··· + r
1k
β
k
= q
1
r
21
β
1
+ r
22
β
2
+ ··· + r
2k
β
k
= q
2
r
J1
β
1
+ r
22
β
2
+ ··· + r
Jk
β
k
= q
J
.
Rβ = q,
R =
r
11
r
12
r
13
. . . r
1k
r
21
r
22
r
23
. . . r
2k
r
J1
r
J2
r
J3
. . . r
Jk
, q =
q
1
q
2
q
J
.
F
F = (R
ˆ
β − q)
T
[s
2
R(X
T
X)
−1
R
T
]
−1
(R
ˆ
β − q)/J,
F [J, n−k] F
β
2
= β
3
= ··· = β
k
= 0 R
(k − 1) × (k − 1) q = 0
F
p
β
0
i
1
β
0
i
2
. . . β
0
i
p
β
i
1
= β
0
i
1
β
i
2
= β
0
i
2
. . .
β
i
p
= β
0
i
p
F

α i = {i
1
, i
2
, . . . , i
p
} β
0
i
= (β
0
i
1
, β
0
i
2
, . . . , β
0
i
p
)
T
ˆ
β
i
=
(
ˆ
β
i
1
, . . . ,
ˆ
β
i
p
)
T
[p, n−k]
F
α
p,n−k
β
0
i
1
p
(
ˆ
β
i
− β
0
i
)
T
d
Var
i
(
ˆ
β)
−1
(
ˆ
β
i
− β
0
i
) ≤ F
α
p,n−k
,
d
Var
i
(
ˆ
β) p × p
ˆ
β
i
˜
β =
ˆ
β − (X
T
X)
−1
R
T
[R(X
T
X)
−1
R
T
]
−1
(R
ˆ
β − q).
Var(
˜
β) = σ
2
(X
T
X)
−1
− σ
2
(X
T
X)
−1
R
T
[R(X
T
X)
−1
R
T
]
−1
R(X
T
X)
−1
σ
2
s
2
˜
e
˜
e = Y − X
˜
β.
F
F =
(
˜
e
T
˜
e − e
T
e)/J
e
T
e/(n − k)
=
(R
2
− R
2
1
)/J
(1 − R
2
)/(n − k)
,
e R
2
R
2
1
F
˜
e
F

F
X
1
Y
1
X
2
Y
2
X
1
X
2
ˆ
β
1
= (X
T
1
X
1
)
−1
X
T
1
Y
T
1
,
ˆ
β
2
= (X
T
2
X
2
)
−1
X
T
2
Y
T
2
.
e
T
e = e
T
1
e
1
+ e
T
2
e
2
.
β
1
= β
2
R = [I, −I] q = 0 Rβ = q
X =
X
1
X
2
, Y =
Y
1
Y
2
,
ˆ
β = (X
T
X)
−1
X
T
Y,
˜
e = Y − X
ˆ
β.
J
X n − k = n
1
+ n
2
− 2k n
1
+ n
2
2k
X
R
=
Z
pre
0 W
pre
0 Z
post
W
post
,
pre post
Z
pre
Z
post
W
pre
W
post

i Z
pre
Z
post
Z
pre
= i
n
1
Z
post
= i
n
2
W
pre
W
post
Y X
R
˜
e J W
pre
=
W
post
X
1
X
2
X
2
n
2
< k
˜
e
X
1
ˆ
β
2
e F
F =
(
˜
e
T
˜
e − e
T
e)/n
1
e
T
e/(n
2
− k)
[n
1
, n
2
− k]
ˆ
β
t−1
β t − 1
t −1 ≥ k e
t
Y
t
e
t
= Y
t
− x
t·
ˆ
β
t−1
,
X
T
2
X
2
k

x
t·
t t
X
w
t
=
e
t
q
1 + x
T
t·
(X
T
t−1
X
t−1
)
−1
x
t·
0 σ
2
X
t−1
((t − 1) × k) t − 1
X
ˆσ
2
=
1
n − k − 1
n
X
t=k+1
(w
t
− w)
2
, w =
1
n − k
n
X
t=k+1
w
t
.
w
t
/ˆσ
w
t
/ˆσ
t
(−2, 2)
W
s
=
s
X
t=k+1
w
t
ˆσ
.
W
s
s − k W
s
s
[k, ±a(n − k)
1/2
]
[k, ±3a(n −k)
1/2
] a
0.948 1.143 95% 99%
f
t
= [x
t
, e
2
t
− e
2
]
T
, e
2
=
1
n
n
X
t=1
e
2
t
.
X
T
e =
n
X
t=1
x
t·
e
t
= 0,
n
X
t=1
(e
2
t
− e
2
) = 0,
n
X
t=1
f
t
= 0.